Morphometric Analysis on Vanniyar Basin in Dharmapuri, Southern India, Using Geo-Spatial Techniques - Suresh, S.; Krishnan, P. (Frontiers in Remote Sensing, 2022)
The Vanniyar basin is located in Dharmapuri district, South India, and is severely affected by climate change. Due to changing climatic conditions and resulting poor precipitation characteristics, this district has received less rainfall over the last three decades (Dharmapuri District Statistical Hand book 2020). The objective of this investigative study is to utilise morphometric techniques and analyse their properties through GIS and image processing techniques. The linear, aerial and relief morphometric aspects of the Vanniyar basin are analysed. From the preliminary investigation, the study area occupies the Archean group of rocks. The drainage pattern of the Vanniyar basin is sub-dendritic to dendritic and classified into fifth-order drainage basins. The mean drainage density of the Vanniyar basin is 1.95 km/km2, which indicates that the basin has very permeable soil with intermediate drainage and low to moderate relief. The circularity ratio value reveals that the basin is circular with high to moderate relief and a structurally controlled drainage system. The elongation ratio value reveals that the basin is characterised by high susceptibility to erosion and sediment load. The stream length ratio between the streams of different orders of the Vanniyar basin shows a change in each sub-basin, indicating late youth stage of geomorphic development. From these research studies, farmers in the Vanniyar basin, river Cauvery may now comprehend their drainage basin's geohydrological characteristics.